The The Impact of a Descriptive Essay on Midwifery Students' Writing Achievement - Pamuji, Arief; wahyudi, Agus; Martuti, Ririn (PT FORMOSA CENDEKIA GLOBAL, 2024)
The objective of this research was survey the students’ ability in writing a descriptive text of midwifery students of STIK Bina Husada and STIKES Aisyiyah. It was a survey research, 40 students majoring Midwifery as the sample of this research taken by using total sampling. The data were obtained by using writing test. To verify the hypotheses, the primary data were analyzed by using pre and post test and paired sample t rest by means of Statistical Product and Service Solution (SPSS) 20th version computer program. Based on the data analysis, the influencing of descriptive essay strategy to the students’ writing on paired sample t test were t-obtained was 6.091. from the data of both places there were improvement of students’ achievement from their pretest to posttest. It can be stated that the descriptive essay strategy can improve the students’ writing achievement.